Modos y planes en el crecimiento urbano de la ciudad de Loja. 1900 - 2013 - Palacios Córdova, Israel Gonzalo (2015)
This paper is an essay that analyzes the process of shaping the city of Loja, related to modes of growth and plans computers urban that existed from 1900 until 2013, considering the history from the founding year 1548. Includes an analysis of the reality of global human habitat and Le Corbusier approaches towards human city; followed by the study of socioeconomic factors in the context and action in the urban history of Ecuador. It contains a historical record of images, maps and plans, which allow and graphically locate the historical reality of the city of Loja in different time periods.